2015
DOI: 10.1155/2015/803942
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Pathogenesis and Its Link to the Mitochondrion

Abstract: Alzheimer's disease (AD) is the most common form of dementia in the elderly. This neurodegenerative disorder is clinically characterized by impairment of cognitive functions and changes in behaviour and personality. The pathogenesis of AD is still unclear. Recent evidence supports some role of mitochondria dysfunction and oxidative stress in the development of the neurodegenerative process. In this review, we discuss the role of mitochondrial dysfunction in AD, focusing on the mechanisms that lead to mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 98 publications
(121 reference statements)
1
29
0
Order By: Relevance
“…Cognitive decline begins before appearance of the dementia syndrome [1], [2] and shares common features with AD and the ageing brain [2].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive decline begins before appearance of the dementia syndrome [1], [2] and shares common features with AD and the ageing brain [2].…”
Section: Introductionmentioning
confidence: 99%
“…To date, mitochondrial respiratory failure and oxidative stress can contribute to cognitive decline (Simoncini et al 2015). It has been reported that MELAS patients without stroke-like episodes can also develop cognitive decline (Finsterer 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that MELAS patients without stroke-like episodes can also develop cognitive decline (Finsterer 2009). The accumulation of somatic mitochondrial DNA mutations accelerates oxidative damage, increases the production of reactive oxygen species, and promotes amyloid accumulation (Simoncini et al 2015). Moreover, recent studies have shown that diabetes itself could be a risk factor for cognitive decline, and a history of severe hypoglycemia is associated with a greater risk of cognitive decline (Whitmer et al 2009;Gudala et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The bioenergy production phenotype of cells can be reprogrammed in response to a variety of stimuli and perturbations5. Dysfunction of mitochondria, which produce bioenergy in form of adenosine triphosphate (ATP) through oxidative phosphorylation (OXPHOS), has been associated with a variety of neurodegenerative diseases, including Alzheimer’s67 and Parkinson’s8. Similarly, alteration in energy metabolism manifested as an upregulation of oxidative glycolysis in cancer cells (Warburg effect) has been recognized as one of the hallmarks of cancer9.…”
mentioning
confidence: 99%